#1**+5 **

**Let $f(x) = 2x+1$ and $g(x) = f(2x) - 3$. What is $g(g(2))$?**

To start this, we see that g(x)=f(2x)-3. So..., we can plug in 4 into f(x). This will give us 9. From there, we subtract 3 and get 6. Repeat the process, but plug in 12 for x in f(x). This will give is 23-3=20. Therefore, g(g(2))=\(\boxed{20}\)

**Wheres CPhill on Leaderboard? :(**

Press the little arrow on the bottom. Then CPhill will show up on the top. (prob because his score is too high, or he has not been on lots, lol)

:)

ilorty Aug 13, 2020